2013
DOI: 10.1016/j.aeolia.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Loess origin, transport, and deposition over the past 10,000years, Wrangell-St. Elias National Park, Alaska

Abstract: a b s t r a c tContemporary glaciogenic dust has not received much attention, because most research has been on glaciogenic dust of the last glacial period or non-glaciogenic dust of the present interglacial period. Nevertheless, dust from modern glaciogenic sources may be important for Fe inputs to primary producers in the ocean. Adjacent to the subarctic Pacific Ocean, we studied a loess section near Chitina, Alaska along the Copper River in Wrangell-St. Elias National Park, where dust has been accumulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 59 publications
7
53
1
Order By: Relevance
“…There is evidence that the oceans south of Iceland are Felimited during and after peak bloom, and the Irminger Basin waters have been identified as an area of low dissolved Fe (Nielsdóttir et al, 2009;Ryan-Keogh et al, 2013). Achterberg et al (2013) found elevated Fe levels in surface waters south of Iceland during the 2010 Eyjafjallajökull eruption, indicating that volcanic activity can raise the oceanic Fe numbers.…”
Section: Oceanic Iron Deposition With Dustmentioning
confidence: 99%
See 3 more Smart Citations
“…There is evidence that the oceans south of Iceland are Felimited during and after peak bloom, and the Irminger Basin waters have been identified as an area of low dissolved Fe (Nielsdóttir et al, 2009;Ryan-Keogh et al, 2013). Achterberg et al (2013) found elevated Fe levels in surface waters south of Iceland during the 2010 Eyjafjallajökull eruption, indicating that volcanic activity can raise the oceanic Fe numbers.…”
Section: Oceanic Iron Deposition With Dustmentioning
confidence: 99%
“…Bullard, 2013), as was witnessed after the 2010 Eyjafjallajökull eruption (Thorsteinsson et al, 2012). Furthermore, some glaciogenic Arctic dust sources are composed of ironrich volcanic deposits, such as in Iceland (Baratoux et al, 2011;Dagsson-Waldhauserova et al, 2013b) and some parts of Alaska (Muhs et al, 2013). In Iceland, these aeolian materials are primarily poorly crystallized basaltic materials (glass) containing high quantities of iron, which can have a substantial impact on the ocean chemistry and fertility.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1b) and abundant production of glaciogenic silt. Holocene loess accumulation has been observed at numerous locations within central and southern Alaska (Péwé, 1975;Muhs et al, 2003Muhs et al, , 2004Muhs et al, , 2013Crusius et al, 2011).…”
Section: Introductionmentioning
confidence: 99%